2023
DOI: 10.52398/gjsd.2023.v3.i2.pp26-33
|View full text |Cite
|
Sign up to set email alerts
|

“Mind the Leadership Gap!”

Liam Murphy,
Helen Turnbull

Abstract: The coronavirus pandemic has acted as a catalyst for organisational change, disrupting historic ways of working, and spearheading organisations towards the next evolution of their working environments. In the aftermath of the largest concurrent work from home experiment in the world, organisations are coming to grips with the new policies and practices they need to implement to remain competitive. But there is one crucial stakeholder who continues to be left out in academic research, leaders. New questions now… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…It is evident from the research presented thus far that the transition towards task-focused work systems, and the gig economy, raise a new dynamic to the leadership gaps we discussed in our previous paper (Murphy and Turnbull, 2023). New questions now arise to further the future research agenda, such as:…”
Section: Future Research Agendamentioning
confidence: 84%
See 2 more Smart Citations
“…It is evident from the research presented thus far that the transition towards task-focused work systems, and the gig economy, raise a new dynamic to the leadership gaps we discussed in our previous paper (Murphy and Turnbull, 2023). New questions now arise to further the future research agenda, such as:…”
Section: Future Research Agendamentioning
confidence: 84%
“…However, scholars have found that increasing a leader's effort to convey emotion often results in a reduced inclination to do so, thus transitioning the employee and leader relationship to a transactional state (Silard et al, 2022). This raises new concerns, since our previous paper in this journal confirmed that younger generations, such as millennials, now seek more personal, one-to-one relationships with their leaders, and reject older transactional forms of leadership (Murphy and Turnbull, 2023). Thus, to counteract the impact of feelings of organisational belonging in a task-focused work environment, it is clear that leaders will need to enhance their humanistic skills, such as their self-awareness, empathy, communication, and listening (Allen et al, 2021).…”
Section: Task-focused Work Systemsmentioning
confidence: 96%
See 1 more Smart Citation